Drug resistance patterns of herpes simplex virus isolates from patients treated with acyclovir. - McLaren, C (1985)
A decrease in the in vitro sensitivity to acyclovir (ACV) was observed in successive isolates of herpes simplex virus type 1 from three immunocompromised patients during intravenous therapy with this drug. The ACV-resistant isolate from patient 1 was cross-resistant to dihydroxypropoxymethylguanine and bromovinyldeoxyuridine, but still susceptible to three fluoro-substituted pyrimidines, 2'-fluoro-5-iodo-1-beta-D-arabinofuranosylcytosine (FIAC), 2'-fluoro-5-iodo-1-beta-D-arabinofuranosyluracil (FIAU), and 2'-fluoro-5-iodo-1-beta-D-arabinofuranosylthymine (FMAU). The thymidine kinase (TK) from the resistant isolate showed a 50-fold or greater reduction in affinity for thymidine, FIAU, FMAU, and ACV, but the total enzyme activity was similar to that of the sensitive isolate. The ACV-resistant isolate from patient 2 was also resistant to dihydroxypropoxymethylguanine, bromovinyldeoxyuridine, and the fluoro-substituted compounds; TK activity for this isolate was less than 1% of the patient's pretherapy isolate. An isolate obtained during a subsequent recurrence in patient 2 was susceptible to ACV and the other TK-dependent agents. The ACV-resistant isolate from patient 3 was partially resistant to FIAC and FIAU but still susceptible to FMAU; the viral TK had a 10-fold-lower affinity for ACV, FIAU, and FMAU than did the sensitive pretherapy isolate, while the level of TK activity detected was reduced to 6%. In none of the isolates studied was a change in sensitivity to phosphonoformic acid observed. Compared with the corresponding pretherapy ACV-sensitive isolates, there was a 30-fold decrease in neurovirulence for mice of the two drug-resistant isolates with diminished levels of thymidine-phosphorylating activity and no change in virulence for the third isolate. These findings indicate that mixed patterns of drug-resistance to TK-dependent antiviral compounds can occur in clinical isolates, resulting from changes in either the amount or the affinity of viral TK activity.